Peran Wakaf Tunai Saat Pandemi Covid-19 di Indonesia - Luluk Latifah; Iskandar Ritonga; Muhammad Lathoif Ghozali; Fatkur Huda (Al Maal: Journal of Islamic Economics and Banking, 2023)
The purpose of this study is to generate a sense of optimism in the community in general and the government in particular in overcoming the economic recession that is hitting Indonesia. This countermeasures by looking at the potential of waqf in Indonesia, especially cash waqf as a role model. This study uses a descriptive qualitative approach. The results show that the cash waqf instrument has enormous benefits during a pandemic like this, both in the economic sector and in the non-economic sector. In the non-economic sector, investment returns from cash waqf can be used to provide direct cash assistance to the community to increase the purchasing power of vulnerable people affected by Covid-19. In the economic sector, cash waqf profit sharing can also be used to provide working capital to MSMEs, to finance infrastructure development and to finance other productive economic businesses, especially for workers who are currently being laid off a lot. In both the economic and non-economic sectors, cash waqf revenue sharing can produce a very large multiplier effect and is beneficial for investors in increasing production, and for the government in increasing government revenue from the tax sector.